تعدد الزوجات بين الإطلاق والتقييد والإلغاء: دراسة فقهية قانونية على ضوء مدونة الأسرة المغربية - LAABID MOHAMMED YASSINE (Journal of Family Law and Islamic Court, 2025)
تأتي هذه الورقة البحثية من أجل بيان مدى توفق المشرع المغربي في تشريع أحكام تعدد الزوجات بما ينسجم مع أحكام التشريع الإسلامي ومقاصده وتحقيق الإنصاف بين الزوجين؛ وذلك من خلال بيان موقف القائلين بإطلاق تعدد الزوجات، ثم إبراز موقف القائلين بتقييد أو إلغاء تعدد الزوجات، ثم بترجيح القول بين الموقفين؛ وقد خلُصَ البحث إلى أنه ينبغي بشكل واضح وبصياغة دقيقة ومحكمة - في الإصلاح الجديد المرتقب لمدونة الأسرة بالمغرب - على الشروط الشرعية والقانونية والمبررات الموضوعية والحالات الاستثنائية التي تستدعي التعدد، وكيفية التحقق من توفرها واقعيا في من يقدِمُ على هذه الخطوة؛ لأن التعدد لم يُشرَع لهوًا وعبثًا وإشباعًا لِنزوة عابرة، ولكن لحفظ كرامة المرأة من الامتهان والاستغلال، وتحقيق مصالح الأسرة واستقرار المجتمع ككل، وفي الوقت نفسه المصالح والأهداف التي قصدها الشارع الحكيم من إباحة تعدد الزوجات.The present paper aims to reveal the extent to which the Moroccan legislator has succeeded in regulating the practice of polygamy in alignment with the principles and objectives of Islamic legislation, while ensuring equity between spouses. The study examines three key perspectives: the first one calls   for the unrestricted practice of polygamy, the second is for its restriction or abolition, while the third perspective tries to balance between, and make use of, the two positions. The research concludes that the anticipated amendments to the Moroccan Family Code should clearly and precisely articulate the legal and Islamic conditions, objective justifications, and exceptional cases necessitating polygamy. It also calls for verifying these conditions in practice for anyone intending to pursue this step. This is because polygamy was not legislated for trivial purposes or fleeting desires but rather to protect women from exploitation and degradation, uphold the dignity of the family, and promote societal stability. Simultaneously, it seeks to achieve the broader objectives intended by Islamic law in permitting polygamy.